USING A GENRE-BASED APPROACH TO PREPARE UNDERGRADUATE STUDENTS FOR AN ENGLISH THESIS DEFENCE EXAMINATION: AN EXPERIMENTAL STUDY TO ADDRESS THE ‘PEDAGOGICAL CONTROVERSY’ - Iskandar Abdul Samad; Zifirdaus Adnan (Masyarakat Linguistik Indonesia, 2017)
A great deal of research has been conducted on genre based approach, suggesting that it is an important approach. Its importance is also indicated by the fact that it is adopted in the 2004 and 2006 National English Curricula of Indonesian secondary schools. However, the pedagogical benefit of this approach to English language teaching is still controversial. Some research has shown that it is effective to develop language competence, some has not. The fact that since the adoption of this approach in the 2004 Indonesian National Curriculum the quality of Indonesian English language teaching at Indonesian schools has not significantly improved complicates the issue further. The present study was intended to contribute to the debate. It is an experiment to discover whether the approach can help improve the performance of students in university thesis defence examinations. The study was conducted at a university level because of an important practical issue, that is complaints among members of the academic community about the poor performance of undergraduate (UG) students in the thesis defence examination (TDE) event at Indonesian universities especially in Aceh. It was believed that even though students were competent in speaking general English, they were poor in their oral thesis defence performance. This study concludes that, with some conditions, it can help at least in some respects.